Karakterisasi Morfologi Pala (Myristica fragrans Houtt) Di Kecamatan Leihitu, Kabupaten Maluku Tengah - Tasane, Serhan; Marzuki, Ilyas; Hukom, Zakarias F M (Jurnal Agrosilvopasture-Tech, 2024)
Nutmeg is an important plantation product in Indonesia which is an important commodity and is stored at the international level (export commodity). This research aims to analyze the morphological and main characteristics of Banda nutmeg plants. Surveys and observations were carried out in Negeri Lima, Seith, Hila, Mamala and Morella, Central Maluku Regency. Based on the HCA cluster analysis, it is known that the 43 plant samples are known to be grouped into two large groups (Group I and II), where Group I consists of two subgroups, namely Ia and Ib. In Subgroup Ia, which consists of 28 plants, the dissimilarity level is 26% (or 74% similarity). Meanwhile, in Subgroup Ib, which only consists of 2 plants, the dissimilarity level is 18.8% (or 81.2% similarity). The second group, which also only consists of 2 plants, has a dissimilarity level of 23% (or 77% similarity). Furthermore, from the analysis of the PCA results, it is known that the morphological diversity of nutmeg is 26.3%, which is reflected in the main morphological characters, namely circumference, stem diameter, fruit stem weight, fruit flesh weight, and fruit diameter.